Case Management Protocol and Declining Blood Lead Concentrations Among Children - Nedra S. Whitehead, PhD, MS; Richard Leiker, MS (Centers for Disease Control and Prevention, 2007)
Introduction Blood lead concentrations among children aged 6 years and younger become a concern at 10 µg/dL (0.48 μmol/L) or higher. The authors' objective was to determine whether initial blood lead concentrations of 10-19 µg/dL (0.48-0.96 μmol/L) declined among children aged 3 years and younger and whether the magnitude of decline was associated with the case management protocol of the state or local childhood lead poisoning prevention program.Methods The authors analyzed childhood blood lead surveillance data from 1994 through 1995 and case management protocols from six states that reported the results of all blood lead tests. The study included 2109 children aged 2 years or younger who had a venous blood lead concentration of 10-19 µg/dL (0.48-0.96 μmol/L) and a follow-up venous blood lead test within 3 to 12 months.Results Overall, blood lead concentrations increased by 0.25 µg/dL (0.01 μmol/L) between the time of the initial elevated blood lead test and the follow-up test, but concentrations declined by 1.96 µg/dL (0.09 μmol/L) among children covered by a case management protocol that included a home visit and by 0.92 µg/dL (0.04 μmol/L) among those covered by a protocol that included a lead source investigation. The decline remained significant after we adjusted for the child's age.Conclusion These findings suggest that childhood lead prevention programs should consider focusing their efforts on home visits and lead source investigations.